ACW-02 an Acridine Triazolidine Derivative Presents Antileishmanial Activity Mediated by DNA Interaction and Immunomodulation - Sonaly Lima Albino; Willian Charles da Silva Moura; Malu Maria Lucas dos Reis; Gleyton Leonel Silva Sousa; Pablo Rayff da Silva; Mayara Gabriele Carvalho de Oliveira; Tatiana Karla dos Santos Borges; Lucas Fraga Friaça Albuquerque; Sinara Mônica Vitalino de Almeida; Maria do Carmo Alves de Lima; Selma Aparecida Souza Kuckelhaus; Igor José dos Santos Nascimento; et al. (Pharmaceuticals, 2023)
The present study proposed the synthesis of a novel acridine derivative not yet described in the literature, chemical characterization by NMR, MS, and IR, followed by investigations of its antileishmanial potential. In vitro assays were performed to assess its antileishmanial activity against L. amazonensis strains and cytotoxicity against macrophages through MTT assay and annexin V-FITC/PI, and the ability to perform an immunomodulatory action using CBA. To investigate possible molecular targets, its interaction with DNA in vitro and in silico targets were evaluated. As results, the compound showed good antileishmanial activity, with IC50 of 6.57 (amastigotes) and 94.97 (promastigotes) µg mL−1, associated with non-cytotoxicity to macrophages (CC50 > 256.00 µg mL−1). When assessed by flow cytometry, 99.8% of macrophages remained viable. The compound induced an antileishmanial effect in infected macrophages and altered TNF-α, IL-10 and IL-6 expression, suggesting a slight immunomodulatory activity. DNA assay showed an interaction with the minor grooves due to the hyperchromic effect of 47.53% and Kb 1.17 × 106 M−1, and was sustained by docking studies. Molecular dynamics simulations and MM-PBSA calculations propose cysteine protease B as a possible target. Therefore, this study demonstrates that the new compound is a promising molecule and contributes as a model for future works.